2001
DOI: 10.1161/01.hyp.38.1.81
|View full text |Cite
|
Sign up to set email alerts
|

Sodium Sensitivity of Blood Pressure Appearing Before Hypertension and Related to Histological Damage in Immunoglobulin A Nephropathy

Abstract: Abstract-Patients with renal parenchymal disease exhibit sodium-sensitive hypertension. We examined patients with immunoglobulin A (IgA) nephropathy to determine whether this sensitivity appears before hypertension begins and whether this sensitivity is related to histological damage. Thirty-eight patients with IgA nephropathy followed a diet with an ordinary sodium level for 1 week and a sodium-restricted diet for 1 week, in random order, and were divided into 3 groups by their systemic blood pressure on the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
38
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(45 citation statements)
references
References 30 publications
7
38
0
Order By: Relevance
“…We recently showed this quantitative relationship in CKD 38,39 and healthy donors after nephrectomy, 40 in both of whom there was an inverse relationship between GFR and the night/day ratio of BP. These findings are compatible with high salt sensitivity of BP in glomerulopathy, even when GFR is maintained at a relatively normal level, 41,42 ultimately becoming much higher as renal function deteriorates. 43,44 These findings are also compatible with the proposal that as the number of nephrons is reduced BP becomes more salt sensitive.…”
Section: Salt Sensitivity and Circadian Rhythm Of Blood Pressuresupporting
confidence: 70%
“…We recently showed this quantitative relationship in CKD 38,39 and healthy donors after nephrectomy, 40 in both of whom there was an inverse relationship between GFR and the night/day ratio of BP. These findings are compatible with high salt sensitivity of BP in glomerulopathy, even when GFR is maintained at a relatively normal level, 41,42 ultimately becoming much higher as renal function deteriorates. 43,44 These findings are also compatible with the proposal that as the number of nephrons is reduced BP becomes more salt sensitive.…”
Section: Salt Sensitivity and Circadian Rhythm Of Blood Pressuresupporting
confidence: 70%
“…We also found that the estimated glomerular capillary pressure (PGC) was elevated in patients with sodium-sensitive essential hypertension and primary aldosteronism (7), a typical form of sodium-sensitive hypertension due to secondary causes. In addition, it has been well established that BP becomes sodium sensitive in patients with chronic glomerulonephritis (8), and sodium sensitivity has also been reported to be greater as the GFR declines (9). These findings strongly support the interrelationships among salt sensitivity, glomerular hypertension, renal damage, and microalbuminuria.…”
Section: Benidipine Attenuates Glomerular Hypertension and Reduces Alsupporting
confidence: 56%
“…Our recent study of patients with IgA nephropathy showed that the sodium sensitivity of blood pressure is significantly correlated with glomerulosclerosis (8). The more the number of glomeruli is decreased, the more blood pressure becomes sodium-sensitive.…”
Section: Discussionmentioning
confidence: 99%
“…Thirty-nine Japanese inpatients with IgA nephropathy participated in this study; the 11 men and 28 women were aged 20 to 59 years. Thirtythree of these patients were described earlier (8). The patients' characteristics are shown in Table 1.…”
Section: Methods Subjectsmentioning
confidence: 99%